Depression and Anxiety in Women During Pregnancy in Slovenia - PODVORNIK, Nuša (Zdr Varst, 2014)
OBJECTIVE: The aim of the study was to evaluate the prevalence of elevated depression and anxiety among pregnant women and to examine its correlation with medical complications and socio-demographic characteristics. METHODS: The study is based on a cross-sectional design of a sample of 348 women in three trimesters of pregnancy who received routine obstetrical care at the University Medical Centre Ljubljana, Department of Obstetrics and Gynaecology. The responding women filled out a questionnaire on socio-demographic variables, the Centre for Epidemiologic Studies Depression Scale CES-D and the State Trait Anxiety Inventory STAI. RESULTS: 21.7% of pregnant women were identified as suffering from elevated depression symptomatology, 15.7% reported high state anxiety and 12.5% had high trait anxiety. No significant differences in depression and anxiety across pregnancy trimesters were found. The women who have suffered from health complications during previous pregnancies showed higher state anxiety; those experiencing complications during their current pregnancy reported more intense symptoms of depression and of state and trait anxiety than women free of complications. Less educated, lower income and mothers of many children in the third pregnancy trimester reported more intensive symptoms of depression and trait anxiety. CONCLUSIONS: Elevated depression and anxiety are frequent among pregnant women. The results draw attention to the need for early detection and treatment of depression and anxiety during pregnancy.